LATE MIOCENE-PLEISTOCENE RECORDS FROM BAIKAL SEDIMENTS: MARKERS FOR PALEOCLIMATIC AND BIOSTRATIGRAPHIC RECONSTRUCTIONS - Williams D.F.; Karabanov E.B.; Prokopenko A.A.; Kuz'min M.I.; Khursevich G.K.; Gvozdkov A.N.; Bezrukova E.V.; Solotchina E.P. (My University, 2001)
The decade of scientific drilling and multidisciplinary studies of lacustrine sedimentary sequences on Lake Baikal has contributed greatly to expansion of our knowledge on the Asian continent response to global climate and regional tectonic changes. This paper is an effort to sum up the available results and to outline the issues of further investigations.
Keywords: Pleistocene; Miocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Miocene